Pengembangan Wisata Desa Adat Penglipuran Terhadap Ekonomi Masyarakat - Desi Wahyu Lihastuti; Najma Alkhayya; Tiara Dwi Yuliani; Atikah Mumpuni (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Penglipuran village is a traditional village and one of the villages in Bangli Regency, Bali. Penglipuran village is one of the villages that has its own uniqueness as a tourist village that is not owned by other villages. This research focuses on the traditional village of Penglipuran using qualitative descriptive analysis method, where the data is taken from research objects consisting of local residents. The result of the study show that the uniqueness of Penglipuran Village covers several aspects, namely Penglipuran Village as an economic driver and on the other hand, the achievement of equal distribution of basic education in Penglipuran Village.